Er maskinoversetting fra nordsamisk nyttig for sørsamisk? - Antonsen, Lene (Nordlyd, 2023)
The article assesses the strengths and weaknesses of a rule-based translation program from North Saami to South Saami. As a tool for translators, the system can contribute to more text being produced in South Saami, both by using North Saami as an intermediary in the translation of texts from Norwegian and Swedish, and by translating texts that are originally written in North Saami. The system may also help teachers in academia to understand texts written by South Saami students. The system is still not good enough, in particular the number of word pairs in the lexicon must be increased considerably to get a better result. The translation is also not robust with respect tolinguistic errors in the North Saami text. The linguistic difference between North Saami and South Saami syntax is big, and one could consider whether it would be appropriate to use a rule-based approach, which allows using information about the sentences' dependencytrees, in order to more easily transform the sentences from North Saami syntax to acceptable South Saami.